Examining patients' acceptance and trust in digital health during COVID-19 using PLS-SEM - Xiang, Qianyu (2022)
The sudden COVID-19 outbreak has raised awareness of the importance and benefits of digital health. To gain insight into patient acceptance and trust in the use of digital healthcare in the context of a pandemic, this study extends a new model based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), with new variables on trust, in the context of the healthcare industry. The questionnaire was then released to consumers with the experience of using digital health, and the 123 data collected were analysed using variance-based partial least squares (PLS-SEM) in a Smart PLS 4.0 environment.